Comparison of dragging ablation and point‐by‐point ablation with a laser balloon on linear lesion formation. (24th August 2020) - Nagase, Takahiko; Kobori, Atsushi; Inaba, Osamu; Sasaki, Yasuhiro; Tomizawa, Naoki; Asano, So; Fukunaga, Hiroshi; Mabuchi, Kei; Inoue, Kanki; Tanizaki, Kohei; Murai, Tatsuya; Iguchi, Nobuo; et al.
Abstract: Introduction: Lesion size and continuity in dragging laser balloon (LB) ablation, which may enable fast and durable pulmonary vein isolation for atrial fibrillation, are unknown. We evaluated the differences in size and continuity of linear lesions formed by dragging ablation and conventional point‐by‐point ablation using an LB in vitro model. Methods and Results: Chicken muscles were cauterized using the first‐generation LB in dragging and point‐by‐point fashion. Dragging ablation was manually performed with different dragging speeds (0.5–2°/s) using an overlap ratio of the beginning and last site during one application at 12 W/20 s and 8.5 W/30 s. Point‐by‐point ablation was performed with 25% and 50% overlap ratios at six energy settings (5.5 W/30 s to 12 W/20 s). Lesion depth, width, and continuity were compared. Lesion continuity was assessed by the surface and deep visible gap degree categorized from 1 (perfect) to 3 (poor). Twenty lesions were evaluated for each ablation protocol. Lesion depth and width in dragging ablation at high power (12 W) were comparable with most measurements in point‐by‐point ablation. Lesion depth and width were smaller at faster‐dragging speed and lower power (8.5 W) in dragging ablation. The surface visible gap degree was better in dragging ablation at all dragging speeds than a 25% overlapped point‐by‐point ablation ( p < .001). Conclusion: Dragging LB ablation at high power provides deep and continuous linear lesion formation comparable with that of point‐by‐point LB ablation. However, lesion depth and width depending on the dragging speed and power.